Entweltlichung – paavst Benedictus XVI hingetõmbepaus - Kurg, Ingmar (Usuteaduslik Ajakiri, 2017)
Entweltlichung - Period of Respite for the Pope Benedict XVI Vatican II (1962-1965) issued the keyword aggiornamento - modernization - when the Roman Catholic Church was a policymaker in a situation where the Church looked forward to renewing its contacts with the meanwhile modernized world that had gone lost for the Church. During the last years of his pontificate Pope Benedict XVI sent a radical message to Church and world, wishing to consolidate the Church for a better missionary capability -thus there appeared a message for Church entitled Entweltlichung that incited after his so-called Freiburg speech (25.09.2011) a large number of public speeches. Entweltlichung (Unworlding) as the pope formulated it, was not a sociological, pol it ical nor legal but the ological category, a nd more spec ideally, missiological one. The actual intention of the Pope’s speech was the mission of the Church, the participation of the Church in the mission of God as a tool of the gospel. Hie requirements to the Church are to be understood on the basis of the mission: on the one hand, keeping the distance with the world, in order to keep the message of the gospel acute, and, on the other hand, to be open to the world, in order to fully contribute to the mission of God.